Smoking and Endothelial Dysfunction - Golbidi, Saeid; Edvinsson, Lars; Laher, Ismail (Current Vascular Pharmacology, 2020)
Cigarette smoking is one of the most important health concerns worldwide. Even though the rate of smoking is declining in developed countries, it is still experiencing growth in developing regions. Many studies have examined the relationship between smoking, as an established risk factor, and cardiovascular diseases. We provide an updated review of the underlying mechanisms of smokinginduced cardiovascular diseases, with a focus on the relationship between smoking and oxidative stress, particularly from the perspective of endothelial cell dysfunction. We review smoking-induced oxidative stress as a trigger for a generalized vascular inflammation associated with cytokine release, adhesion of inflammatory cells and, ultimately, disruption of endothelial integrity as a protective barrier layer. We also briefly discuss the harms related to the vaping of electronic cigarettes, which many erroneously consider as a safe alternative to smoking. We conclude that even though e-cigarette could be a helpful device during the transition period of cigarette quitting, it is by no means a safe substitute.
Keywords: e-cigarette